Republic of Belarus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
The analysis of inflation developments in Belarus is hampered by widespread price controls. Persistence of common inflation is generally higher than that of actual inflation. Factor analysis assumes that covariation among time series can be explained by a few unobserved shocks (factors). The dependent variable in our estimations is growth in real GDP per capita in purchasing power parity (PPP) terms, while the explanatory variable of interest is the annual rate of change in the terms of trade.